REGIONAL GOVERNMENT FINANCIAL MANAGEMENT IN JAKARTA AND SURABAYA 2016-2021 WHICH IS BETTER? - Abu Bakar; Muliyati Muliyati; Alfan Bachtiar; Memorianus Amazihono (Jurnal Wahana Bina Pemerintahan, 2026)
This study aims to describe and analyze the financial performance of the DKI Jakarta and Surabaya Regional Governments in terms of effectiveness and effectiveness of budget use and growth in local revenue performance as well as aggregate excellence. This study uses a comparative quantitative description method of two governments compared to each other with a regional government financial management approach. The results of the study partially show that the level of effectiveness of the Surabaya regional government is more effective in budget use compared to the DKI Jakarta Regional Government with a ratio of 29:19. In terms of budget efficiency, the DKI Jakarta Regional Government shows much better than the Surabaya Regional Government with a ratio of 17 to 9 but in terms of financial performance growth the Surabaya Regional Government is slightly better than the DKI Jakarta Regional Government with a ratio of 14 to 12. In aggregate, the DKI Jakarta Regional Government is still below the Surabaya Regional Government with achievements of 48 and 52 respectively. This study compares the financial performance of the two governments head to head with the same period and measuring instrument which has never been done in previous research in Indonesia. This study is also for a period of financial responsibility for eight years (2014-2021). The findings in this study show that with smaller assets, the financial management of the Surabaya Government is not automatically more efficient than the financial management of the DKI Jakarta Regional Government, even though they are the same in terms of growth